An engineered extraplastidial pathway for carotenoid biofortification of leaves. Issue 5 (12th March 2021) - Andersen, Trine B.; Llorente, Briardo; Morelli, Luca; Torres‐Montilla, Salvador; Bordanaba‐Florit, Guillermo; Espinosa, Fausto A.; Rodriguez‐Goberna, Maria Rosa; Campos, Narciso; Olmedilla‐Alonso, Begoña; Llansola‐Portoles, Manuel J.; Pascal, Andrew A.; Rodriguez‐Concepcion, Manuel
Summary: Carotenoids are lipophilic plastidial isoprenoids highly valued as nutrients and natural pigments. A correct balance of chlorophylls and carotenoids is required for photosynthesis and therefore highly regulated, making carotenoid enrichment of green tissues challenging. Here we show that leaf carotenoid levels can be boosted through engineering their biosynthesis outside the chloroplast. Transient expression experiments in Nicotiana benthamiana leaves indicated that high extraplastidial production of carotenoids requires an enhanced supply of their isoprenoid precursors in the cytosol, which was achieved using a deregulated form of the main rate‐determining enzyme of the mevalonic acid (MVA) pathway. Constructs encoding bacterial enzymes were used to convert these MVA‐derived precursors into carotenoid biosynthetic intermediates that do not normally accumulate in leaves, such as phytoene and lycopene. Cytosolic versions of these enzymes produced extraplastidial carotenoids at levels similar to those of total endogenous (i.e. chloroplast) carotenoids. Strategies to enhance the development of endomembrane structures and lipid bodies as potential extraplastidial carotenoid storage systems were not successful to further increase carotenoid contents. Phytoene was found to be more bioaccessible when accumulated outside plastids, whereas lycopene formed cytosolic crystalloids very similar to those found in the chromoplasts of ripe tomatoes. This extraplastidial production of phytoene and lycopene led to an increased antioxidant capacity of leaves. Finally, we demonstrate that our system can be adapted for the biofortification of leafy vegetables such as lettuce.